Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To find the [tex]\( n \)[/tex]-th term [tex]\( a_n \)[/tex] of the sequence where the [tex]\( n \)[/tex]-th partial sum is given by
[tex]\[ S_n = \sum_{k=1}^n \left( 6k + 2 \right), \][/tex]
we need to analyze the given sum.
1. Understand the given partial sum expression:
[tex]\[ S_n = \sum_{k=1}^n \left( 6k + 2 \right). \][/tex]
2. Simplify the sum:
Let's break down the sum by splitting it into two parts:
[tex]\[ S_n = \sum_{k=1}^n 6k + \sum_{k=1}^n 2. \][/tex]
3. Evaluate each part of the sum separately:
- The first part [tex]\( \sum_{k=1}^n 6k \)[/tex] is a sum of an arithmetic series:
[tex]\[ \sum_{k=1}^n 6k = 6 \sum_{k=1}^n k = 6 \cdot \frac{n(n+1)}{2} = 3n(n+1). \][/tex]
- The second part [tex]\( \sum_{k=1}^n 2 \)[/tex] is simply [tex]\( 2 \)[/tex] added [tex]\( n \)[/tex] times:
[tex]\[ \sum_{k=1}^n 2 = 2n. \][/tex]
4. Combine the results:
[tex]\[ S_n = 3n(n+1) + 2n. \][/tex]
5. Simplify the combined expression:
[tex]\[ S_n = 3n^2 + 3n + 2n = 3n^2 + 5n. \][/tex]
6. Find the [tex]\( n \)[/tex]-th term [tex]\( a_n \)[/tex]:
The [tex]\( n \)[/tex]-th term of the sequence [tex]\( a_n \)[/tex] is given by [tex]\( S_n - S_{n-1} \)[/tex]:
[tex]\[ a_n = S_n - S_{n-1}. \][/tex]
7. Express [tex]\( S_{n-1} \)[/tex]:
Substitute [tex]\( n-1 \)[/tex] into the partial sum formula:
[tex]\[ S_{n-1} = 3(n-1)^2 + 5(n-1) = 3(n^2 - 2n + 1) + 5n - 5 = 3n^2 - 6n + 3 + 5n - 5 = 3n^2 - n - 2. \][/tex]
8. Calculate the difference [tex]\( S_n - S_{n-1} \)[/tex]:
[tex]\[ a_n = (3n^2 + 5n) - (3n^2 - n - 2) = 3n^2 + 5n - 3n^2 + n + 2 = 6n + 2. \][/tex]
Therefore, the [tex]\( n \)[/tex]-th term of the sequence [tex]\( a_n \)[/tex] is
[tex]\[ \boxed{6n + 2}. \][/tex]
[tex]\[ S_n = \sum_{k=1}^n \left( 6k + 2 \right), \][/tex]
we need to analyze the given sum.
1. Understand the given partial sum expression:
[tex]\[ S_n = \sum_{k=1}^n \left( 6k + 2 \right). \][/tex]
2. Simplify the sum:
Let's break down the sum by splitting it into two parts:
[tex]\[ S_n = \sum_{k=1}^n 6k + \sum_{k=1}^n 2. \][/tex]
3. Evaluate each part of the sum separately:
- The first part [tex]\( \sum_{k=1}^n 6k \)[/tex] is a sum of an arithmetic series:
[tex]\[ \sum_{k=1}^n 6k = 6 \sum_{k=1}^n k = 6 \cdot \frac{n(n+1)}{2} = 3n(n+1). \][/tex]
- The second part [tex]\( \sum_{k=1}^n 2 \)[/tex] is simply [tex]\( 2 \)[/tex] added [tex]\( n \)[/tex] times:
[tex]\[ \sum_{k=1}^n 2 = 2n. \][/tex]
4. Combine the results:
[tex]\[ S_n = 3n(n+1) + 2n. \][/tex]
5. Simplify the combined expression:
[tex]\[ S_n = 3n^2 + 3n + 2n = 3n^2 + 5n. \][/tex]
6. Find the [tex]\( n \)[/tex]-th term [tex]\( a_n \)[/tex]:
The [tex]\( n \)[/tex]-th term of the sequence [tex]\( a_n \)[/tex] is given by [tex]\( S_n - S_{n-1} \)[/tex]:
[tex]\[ a_n = S_n - S_{n-1}. \][/tex]
7. Express [tex]\( S_{n-1} \)[/tex]:
Substitute [tex]\( n-1 \)[/tex] into the partial sum formula:
[tex]\[ S_{n-1} = 3(n-1)^2 + 5(n-1) = 3(n^2 - 2n + 1) + 5n - 5 = 3n^2 - 6n + 3 + 5n - 5 = 3n^2 - n - 2. \][/tex]
8. Calculate the difference [tex]\( S_n - S_{n-1} \)[/tex]:
[tex]\[ a_n = (3n^2 + 5n) - (3n^2 - n - 2) = 3n^2 + 5n - 3n^2 + n + 2 = 6n + 2. \][/tex]
Therefore, the [tex]\( n \)[/tex]-th term of the sequence [tex]\( a_n \)[/tex] is
[tex]\[ \boxed{6n + 2}. \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.